1999
DOI: 10.1185/03007999909115171
|View full text |Cite
|
Sign up to set email alerts
|

Hypericumin Seasonal Affective Disorder (SAD)

Abstract: Volunteers from the membership of the SAD Association took part in a postal survey, before and after eight weeks' treatment with Hypericum (Kira), using an 11-item rating scale. The maximum score is 44 and the mean score in 168 patients using Kira alone was 21.3. This fell to 13 at endpoint (p < 0.001). The corresponding figures for 133 patients using Kira + light therapy were 20.6 and 11.8, respectively (p < 0.001). In both groups, there was significant improvement in anxiety, loss of libido and insomnia. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 10 publications
2
18
0
3
Order By: Relevance
“…The results suggested that SJW alone may achieve a similar efficacy to that of the combination 34 . These data seem to be confirmed by another study that found that Kira (a hypericum preparation) in monotherapy produced significant relief of SAD symptoms and that the addition of light therapy did not cause further significant improvement 35 . Despite the abundance of short-term trials, the efficacy of SJW has not yet been studied systematically in patients with psychotic depression, geriatric depression (where response rate may be lower and delayed), bipolar depression (where the primary treatment is mood stabilizer and there is a risk of increased mania with some antidepressants), premenstrual dysphoric disorder, dysthymia or double depression.…”
supporting
confidence: 73%
“…The results suggested that SJW alone may achieve a similar efficacy to that of the combination 34 . These data seem to be confirmed by another study that found that Kira (a hypericum preparation) in monotherapy produced significant relief of SAD symptoms and that the addition of light therapy did not cause further significant improvement 35 . Despite the abundance of short-term trials, the efficacy of SJW has not yet been studied systematically in patients with psychotic depression, geriatric depression (where response rate may be lower and delayed), bipolar depression (where the primary treatment is mood stabilizer and there is a risk of increased mania with some antidepressants), premenstrual dysphoric disorder, dysthymia or double depression.…”
supporting
confidence: 73%
“…Evidence exists from placebo-controlled trials that HE shows efficacy in patients with depressive disorders accompanied by fatigue (Halama, 1991 ;Sommer and Harrer, 1994), whereas open studies report its effect in seasonal affective disorder (Kasper, 1997 ;Martinez et al, 1994 ;Wheatley, 1999). Apart from the RVS, atypical depression is characterized by 'leaden paralysis of the limbs' (i.e.…”
Section: Introductionmentioning
confidence: 94%
“…The effects of St John's wort extracts have been investigated in studies involving subjects with seasonal affective disorder (SAD) (Kasper 1997 ;Wheatley 1999), although as yet there have not been any trials that have included a placebo control group. Twenty individuals with SAD were randomised to receive St John's wort (LI 160) 300 mg three times daily (equivalent to hypericin 0.9 mg) with or without bright light therapy (Kasper 1997).…”
Section: Seasonal Affective Disordermentioning
confidence: 99%
“…After 4 weeks, there were significant reductions in HAMD scores in both groups, compared with baseline values ; there were no statistically significant differences between groups. Another study evaluated data from individuals with mild-to-moderate SAD who had used St John's wort 300 mg three times daily (equivalent to 0.9 mg hypericin), with (n l 133) or without light therapy (n l 168), for 8 weeks (Wheatley 1999). The study was not randomised and involved data collection by postal questionnaires.…”
Section: Seasonal Affective Disordermentioning
confidence: 99%